Zonal human hepatocytes are differentially permissive to Plasmodium falciparum malaria parasites. (18th January 2021) - Yang, Annie S P; van Waardenburg, Youri M; van de Vegte‐Bolmer, Marga; van Gemert, Geert‐Jan A; Graumans, Wouter; de Wilt, Johannes H W; Sauerwein, Robert W
Abstract: Plasmodium falciparum ( Pf ) is a major cause of human malaria and is transmitted by infected Anopheles mosquitoes. The initial asymptomatic infection is characterized by parasite invasion of hepatocytes, followed by massive replication generating schizonts with blood‐infective merozoites. Hepatocytes can be categorized by their zonal location and metabolic functions within a liver lobule. To understand specific host conditions that affect infectivity, we studied Pf parasite liver stage development in relation to the metabolic heterogeneity of fresh human hepatocytes. We found selective preference of different Pf strains for a minority of hepatocytes, which are characterized by the particular presence of glutamine synthetase (hGS). Schizont growth is significantly enhanced by hGS uptake early in development, showcasing a novel import system. In conclusion, Pf development is strongly determined by the differential metabolic status in hepatocyte subtypes. These findings underscore the importance of detailed understanding of hepatocyte host‐ Pf interactions and may delineate novel pathways for intervention strategies. SYNOPSIS: In vitro studies of the liver stage of malaria parasite Plasmodium falciparum ( Pf ) are hampered by low rates of infection and development in cultured hepatocytes. Here, particular human hepatocyte subtypes are shown to be differentially permissive for development of Pf schizonts, suggesting new avenues for in vitro infection model improvements to study the biology of this complex parasite life‐cycle stage. Two distinct Pf strains NF135 and NF175 show selective preference for a hepatocyte subtype that specifically expresses glutamine synthetase. Widely used standard Pf strain NF54 shows an apparent reduced preference for glutamine synthetase‐expressing hepatocytes and concomitantly relatively diminished intra‐hepatic development. Host glutamine synthetase is taken up by intra‐hepatic parasites during early development. Degree of glutamine synthetase expression/uptake correlates with larger schizont size. Abstract : Development of P. falciparum parasites benefits from infection of a glutamine synthase‐expressing subpopulation of human hepatocytes, suggesting avenues for in vitro infection model improvement and better understanding of host‐parasite interactions.